Healthcare waste characteristics and management in Kumasi, Ghana - Oduro-Kwarteng, Sampson; Addai, Rainsford; Essandoh, Helen (Elsevier, 2021)
The healthcare waste management in developing countries has shortfalls compared with international best practices. The main purpose of this study was to assess the generation rate, composition and practices of healthcare waste management (HWM) in Kumasi, Ghana. Healthcare waste samples were collected from four hospitals and three healthcare centres for waste generation, composition and bulk density analyses. The average waste generation rates of the hospitals ranged from 0.76 to 2.92 kg/bed-day and that of the community health centres ranged from 0.012 to 0.08 kg/patient-day. The compositions of the general healthcare and hazardous healthcare waste were 49.65% and 50.35% respectively. The hazardous healthcare waste far exceeded the World Health Organization threshold of within 10 – 25% as a result of inadequate segregation. The facilities had no specific HWM framework and did not comply with best practices. The lack of National regulatory framework for HWM may compromise the prevention of disease transmission.
Scientific African Volume 12, July 2021, e00784
Keywords: Healthcare waste; Healthcare waste management; Waste composition; Solid waste management; Waste behaviour; STEM; University of Port Harcourt